Neo-synthesis of estrogenic or androgenic neurosteroids determine whether long-term potentiation or depression is induced in hippocampus of male rat - Di Mauro, Michela; Tozzi, Alessandro; Calabresi, Paolo; Pettorossi, Vito E.; Grassi, Silvarosa (Frontiers in Cellular Neuroscience, 2015)
Estrogenic and androgenic steroids synthesized in the brain may rapidly modulate synaptic plasticity interacting with specific membrane receptors. We explored by electrophysiological recordings in hippocampal slices of male rat the influence of 17b-estradiol (E2) and 5a-dihydrotestosterone (DHT) neo-synthesis on the synaptic changes induced in the CA1 region. Induction of long-term depression (LTD) and depotentiation (DP) by low frequency stimulation (LFS, 15 min-1 Hz) and of long-term potentiation (LTP) by high (HFS, 1 s-100 Hz), medium (MFS, 1 s-50 Hz), or weak (WFS, 1 s-25 Hz) frequency stimulation was assayed under inhibitors of enzymes converting testosterone (T) into DHT (5a-reductase) and T into E2 (P450-aromatase). We found that LFS-LTD depends on DHT synthesis, since it was fully prevented under finasteride, an inhibitor of DHT synthesis, and rescued by exogenous DHT, while the E2 synthesis was not involved. Conversely, the full development of HFS-LTP requires the synthesis of E2, as demonstrated by the LTP reduction observed under letrozole, an inhibitor of E2 synthesis, and its full rescue by exogenous E2. For intermediate stimulation protocols DHT, but not E2 synthesis, was involved in the production of a small LTP induced by WFS, while the E2 synthesis was required for the MFS-dependent LTP. Under the combined block of DHT and E2 synthesis all stimulation frequencies induced partial LTP. Overall, these results indicate that DHT is required for converting the partial LTP into LTD whereas E2 is needed for the full expression of LTP, evidencing a key role of the neo-synthesis of sex neurosteroids in determining the direction of synaptic long-term effects.